KONSEP DESAIN SISTEM LANDFILL SAMPAH, SISTEM PEMURNIAN GAS, DAN SISTEM TANGKI PENAMPUNG UNTUK TEMPAT PEMBUANGAN SAMPAH TERPADU (TPST) PIYUNGAN BANTUL YOGYAKARTA - , KHOIRIYATI KAULINA R, Rachmawan Budiarto, S.T., M.T. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Landfills with open dumping process resulted in problems such as global warming. Methane is a gas produced from landfills as much as 50-55 % of the entire volume of gas produced and has the potential to cause global warming 21- 23 times greater than CO2. TPST Piyungan is a landfill in Yogyakarta that is still using the controlled landfill in waste management. Therefore, further analysis is needed to determine the potency of methane gas that can be produced in zone III TPST Piyungan as a means of energy alternative and the utilization of existing waste by creating design concepts landfill waste systems, gas purification systems and gas holder system as a preliminary condition to the design of landfill gas for TPST Piyungan Bantul, Yogyakarta . Estimated production of methane produced in 2020 by the waste that goes to the dump site Piyungan year 2007-2017 is 9,983,450.15 m3/year or 0.32 m3/s. Methane gas production for each well is 0.015 m3/s with a number of vertical extraction wells 12 pieces, and the average distance between wells is 100 m . Gas purification system is a system that is applied to the filter system with Solid H2S Scavenger System in which to wash off 1 kg of H2S gas it takes 5 kg of Fe2O3. In CO2 filter system, solution that is flowed is calcium hydroxide (Ca(OH)2), with a flow rate of 900 ml/min, and the water vapor filter system that uses zeolite. The volume needed is 1634.53 m3 (Ï = 4 hours), the design of the system is a gas reservoir radius of base is 6 m and height is 7.3 m with number 2 pieces, each of which has a capacity of 825.2 m3.